Further Analysis of Burkholderia pseudomallei MF2 and Identification of Putative Dehalogenase Gene by PCR - Mohamed Faraj Edbeib; Roswanira Abdul Wahab; Fahrul Zaman Huyop; Hasan Murat Aksoy; Yilmaz Kaya (Universitas Gadjah Mada, 2020)
Halogenated organic compounds are extensively and widely used as pesticides, herbicides, and antibiotics that contribute to the pollution. This research was aimed to further analyze and characterize a bacterium that has the ability to utilize 2,2-dichloropropionic acid (2,2-DCP) as a model to study dehalogenase enzyme production. Microscopic observation, biochemical tests and PCR technique were carried out in order to characterize the isolated bacterium. Strain MF2 showed its ability to grow on 10 mM 2,2-DCP liquid minimal medium with doubling time of 13 h with maximum chloride ion released of 19.8 molCl–/mL. The 16S rDNA analysis suggested that strain MF2 belongs to the genus Burkholderia. This was supported by the microscopic observation and biochemical tests. Dehalogenase gene was observed when using only primers dehIfor1 and dehIrev2 derived from group I deh PCR primer sequences, whereas no amplification using dhlB-314-forward and dhlB-637-reverse (group II dehalogenase) and haloacetate dehalogenase (H2-1157-forward and H2-1662-reverse) PCR primer sequences. The results suggested that, possibly, dehalogenase from MF2 was related to group I deh. In conclusion, strain MF2 showed the ability to utilize 2,2-DCP as sole source of carbon and energy. Further analysis revealed the MF2 strain consisted of dehalogenase gene that could be used for degradation of man-made halogenated compounds present in the environment. Using existing dehalogenase PCR primers, it was possible to amplify the dehalogenase genes sequence.